2014
DOI: 10.1021/jp503718v
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence for Blue-Shifted Hydrogen Bonding in the Fluoroform–Hydrogen Chloride Complex: A Matrix-Isolation Infrared and ab Initio Study

Abstract: The 1:1 hydrogen-bonded complex of fluoroform and hydrogen chloride was studied using matrix-isolation infrared spectroscopy and ab initio computations. Using B3LYP and MP2 levels of theory with 6-311++G(d,p) and aug-cc-pVDZ basis sets, the structures of the complexes and their energies were computed. For the 1:1 CHF3-HCl complexes, ab initio computations showed two minima, one cyclic and the other acyclic. The cyclic complex was found to have C-H · · · Cl and C-F · · · H interactions, where CHF3 and HCl sub-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 74 publications
(94 reference statements)
3
18
0
Order By: Relevance
“…Rather than the red shift of the OH stretching frequency in the water dimer,t he CH stretchs hifts to the blue. This reversal of the usual pattern in the case of CH···O HBs is not unexpected, based on numerous reports [21,[67][68][69][70][71][72] in the literature for this and similar systems. More importantly,j ust as in the case of the water dimer,t he trendsi nb oth Ds and Dn become more pronounced as the CH 4 andO H 2 molecules are squeezed together,a nd the potential reverses from attractive to repulsive.…”
Section: H-bondcontraction and Misorientationsupporting
confidence: 73%
“…Rather than the red shift of the OH stretching frequency in the water dimer,t he CH stretchs hifts to the blue. This reversal of the usual pattern in the case of CH···O HBs is not unexpected, based on numerous reports [21,[67][68][69][70][71][72] in the literature for this and similar systems. More importantly,j ust as in the case of the water dimer,t he trendsi nb oth Ds and Dn become more pronounced as the CH 4 andO H 2 molecules are squeezed together,a nd the potential reverses from attractive to repulsive.…”
Section: H-bondcontraction and Misorientationsupporting
confidence: 73%
“…Spectroscopic measurements offer a second opportunity to examine a system for possible HBs. Within the context of IR and Raman spectra, the stretching frequency of the A-H covalent bond commonly undergoes a substantial red shift, and the band is intensified and broadened (this pattern can be reversed in certain HBs, largely those involving the CH donor [26,27,28,29,30]). The NMR signal of the bridging proton typically shifts downfield by several ppm upon formation of a HB [20,21,31].…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of 'blue-shiing hydrogen bonding', where the stretching frequency of X-H (n X-H ) is shied to a higher value in a hydrogen bonded X-H/Y type cluster, has been extensively discussed in recent literature. In most of the studies reported to date, a very weakly acidic C-H group has been shown to display blue-shiing H-bonding either with classical acceptors, i.e., the electronegative atom Y having lone pair(s) of electrons [5][6][7][8][11][12][13][14][15][16][17][18][19][20]22,23,[25][26][27][29][30][31][32] or non-classical acceptors with p-electron systems, e.g., aromatic group. 6,14,25 The proposed mechanisms, with many different approaches, were aimed at shortening of X-H bond, and the blue shi of n X-H was considered a direct consequence of X-H bond shortening.…”
mentioning
confidence: 99%